PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA PERUSAHAAN (studi empiris pada peusahaan non manufaktur yang terdaftar di BEI TAHUN 2015-2018) - anggia rahma (Jurnal Kajian Akuntansi dan Auditing, 2021)
This study aims to prove and analyze the effect of intellectual capital on the productivity of non-manufacturing companies on the Indonesia Stock Exchange for the period 2015 to 2018. The data used are secondary data. The data analysis method used is multiple regression and t-statistical testing based on the results of hypothesis testing, it is found that human capital efficiency and capital structural efficiency have an effect on the profitability of non-manufacturing companies on the Indonesia Stock Exchange, while structural human capital efficiency has no significant effect on the profitability of non-manufacturing companies. manufacturing on the Indonesia Stock Exchange.